Sealant, and structure

JP2023177469A5Active Publication Date: 2025-01-10SEKISUI CHEMICAL CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022090158
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-06-02
Publication Date
2025-01-10
Estimated Expiration
2042-06-02

AI Technical Summary

Technical Problem

Conventional sealing materials in structures deteriorate over time, leading to interfacial peeling and water leakage due to seasonal changes and external stress, requiring frequent repairs.

Method used

A sealing material comprising a resin and an ion-releasing compound that generates poorly water-soluble salts with specific gravity of 2.0 or more and solubility of 1.0 × 10^-3 mol/L or less, enhancing the durability and waterproofness of the sealed area by forming a denser layer.

Benefits of technology

The sealing material maintains the structure in a stable state for a long period by preventing water leakage and suppressing deterioration, contributing to preventive maintenance of both new and existing structures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

To provide a sealant capable of keeping a structure in a stable state for a long time by heightening waterproofness of a sealed place and its surrounding area.SOLUTION: A sealant pertaining to the present invention includes: a resin; and an ion-emitting compound capable of emitting a cation or an anion, where the ion-emitting compound can generate a water-insoluble salt, the specific gravity of the water-insoluble salt is 2.0 or more, and the solubility of the water-insoluble salt to water at 20°C is 1.0×10-3 mol / L or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a sealant that can be used in structures, and also to a structure using the sealant. [Background technology]

[0002] In structures such as buildings, tunnels, and subways, sealants are sometimes used to improve waterproofing in cracks in the structures, gaps (gaps) at joints between components, etc. Examples of such sealants include silicone-based sealants, urethane-based sealants, and acrylic-based sealants.

[0003] Patent Document 1 listed below discloses a polyurethane resin composition for sealing that contains a castor oil-based polyol, a plasticizer, an amine catalyst, a foam stabilizer, and an organic polyisocyanate, but does not contain polyoxypropylene glycol.

[0004] Patent Document 2 below discloses a composite sheet including a plurality of waterproof sheets and a repair sheet disposed between the waterproof sheets. In this composite sheet, the repair sheet contains a binder resin and a water-absorbent polymer, and the content of the water-absorbent polymer per 100 parts by weight of the binder resin is within a specific range. Patent Document 2 above describes that if a hole opens in the waterproof sheet and causes a water leak, the repair sheet will close the hole and repair the leak. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] WO2015 / 147125A1 [Patent Document 2] Japanese Patent Application Laid-Open No. 2005-066461 Summary of the Invention [Problem to be solved by the invention]

[0006] When conventional sealing materials such as those described in Patent Documents 1 and 2 are used to seal gaps (gaps) in a structure, water leakage from the sealed area can be prevented (waterproofing can be improved) for a certain period of time after sealing.

[0007] However, with conventional sealants, the resin components gradually deteriorate, which can lead to interfacial peeling at the interface between the sealant and the structure. Seasonal fluctuations, repeated vibrations, and expansion and contraction can also cause interfacial peeling at the interface between the sealant and the structure. Therefore, with conventional sealants, if new cracks or tiny voids appear in the structure or ground around the sealed area due to external stress or changes in environmental conditions after sealing, water leakage will occur, requiring repairs.

[0008] Conventionally, there is no known method for repairing or strengthening existing structures and the surrounding areas of the structures in a self-healing manner over a long period of time.

[0009] An object of the present invention is to provide a sealant that improves the waterproofing of the sealed area and its surroundings, and can maintain a structure in a stable state for a long period of time. Another object of the present invention is to provide a structure using the sealant. [Means for solving the problem]

[0010] According to a broad aspect of the present invention, there is provided a method for producing a poorly water-soluble salt comprising the steps of: (a) providing a resin; and (b) providing an ion-releasing compound capable of releasing cations or anions; (c) providing a poorly water-soluble salt having a specific gravity of 2.0 or more and a solubility in water of 1.0×10 at 20° C.; -3 mol / L or less.

[0011] In a specific aspect of the sealant according to the present invention, the poorly water-soluble salt is calcium carbonate, barium carbonate, calcium phosphate, or iron hydroxide.

[0012] In a specific aspect of the sealant according to the present invention, the ion-releasing compound includes a compound capable of releasing cations, and the compound capable of releasing cations is calcium silicate, tricalcium silicate, dicalcium silicate, calcium aluminate, calcium aluminoferrite, calcium hydroxide, calcium oxide, calcium acetate, calcium lactate, barium lactate, calcium sulfate, calcium chloride, calcium nitrate, or calcium bicarbonate.

[0013] In a specific aspect of the sealant according to the present invention, the ion-releasing compound includes a compound capable of releasing an anion, and the compound capable of releasing an anion is sodium hydrogen phosphate, potassium carbonate, potassium hydrogen carbonate, ammonium carbonate, ammonium hydrogen carbonate, sodium carbonate, sodium hydrogen carbonate, or calcium hydrogen carbonate.

[0014] In a specific aspect of the sealant according to the present invention, the resin includes a thermoplastic resin.

[0015] In a specific aspect of the sealant according to the present invention, the resin includes a curable resin.

[0016] According to a broad aspect of the present invention, there is provided a structure comprising a sealing object having a sealing target portion and a sealing material disposed in the sealing target portion, the sealing material being formed from the above-mentioned sealing material. [Effects of the Invention]

[0017] The sealant according to the present invention includes a resin and an ion-releasing compound capable of releasing cations or anions. In the sealant according to the present invention, the ion-releasing compound is capable of generating a poorly water-soluble salt. In the sealant according to the present invention, the poorly water-soluble salt has a specific gravity of 2.0 or more and a solubility in water at 20°C of 1.0 x 10 -3The sealant according to the present invention has the above-mentioned configuration, and therefore can improve the waterproofing of the sealed area and its surroundings, and can maintain the structure in a stable state for a long period of time. [Brief explanation of the drawings]

[0018] [Figure 1] FIG. 1 is a schematic diagram for explaining an example of a method for manufacturing a structure using a sealing material according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE INVENTION

[0019] The present invention will be described in detail below.

[0020] (sealant) The sealant according to the present invention contains a resin and an ion-releasing compound capable of releasing cations or anions (hereinafter, sometimes referred to as "ion-releasing compound"). In the sealant according to the present invention, the ion-releasing compound is capable of generating a poorly water-soluble salt. In the sealant according to the present invention, the poorly water-soluble salt has a specific gravity of 2.0 or more and a solubility in water at 20°C of 1.0 x 10 -3 The sealant according to the present invention is a sealant for generating a poorly water-soluble salt.

[0021] The sealant according to the present invention has the above-described configuration, and therefore can improve the waterproofing of the sealed area and its surroundings, and can maintain the structure in a stable state for a long period of time. More specifically, when the sealant is placed in the area to be sealed of the object to be sealed, the ion-releasing compound in the sealant releases ions, generating poorly water-soluble salts and forming concretions. This densifies the sealed area and its surroundings, effectively preventing water leakage (improving waterproofing), and maintaining the structure in a stable state for a long period of time (increasing durability). The present invention contributes to the preventive maintenance of structures. The present invention contributes to the preventive maintenance of both newly constructed and existing structures.

[0022] In the sealant according to the present invention, when the sealant comes into contact with moisture or the like adhering to the ground or a structure at a sealed location, the ion-releasing compound in the sealant releases ions, thereby generating a poorly water-soluble salt at the contact surface between the sealant and the moisture or the like. That is, the sealant according to the present invention can generate a layer of poorly water-soluble salt on the surface of the sealant. The generated poorly water-soluble salt further increases the strength of the sealed location and its surroundings. The generated poorly water-soluble salt is generally thought to be generated over several months to several years. The generated poorly water-soluble salt effectively prevents further contact between the sealant and moisture, thereby effectively preventing deterioration of the sealant and the structure. When the resin in the sealant contains a curable resin, the generated poorly water-soluble salt can effectively prevent deterioration of the sealant after the curing reaction of the curable resin, thereby effectively preventing deterioration of the cured product (sealed product) of the sealant. Furthermore, when the resin in the sealing material contains a thermoplastic resin, the resulting poorly water-soluble salt can effectively suppress deterioration of the sealing material after molding, thereby effectively suppressing deterioration of the molded body (sealed product) of the sealing material.

[0023] In the sealing material, the poorly water-soluble salt has a specific gravity of 2.0 or more. From the viewpoint of further improving durability against external stress, the poorly water-soluble salt has a specific gravity of preferably 2.1 or more, more preferably 2.2 or more, even more preferably 2.5 or more, and preferably 5.0 or less, more preferably 4.5 or less, even more preferably 3.5 or less.

[0024] The specific gravity of the poorly water-soluble salt can be measured by the liquid immersion method using an electronic balance precision specific gravity meter, such as the "Electronic Specific Gravimeter EDM2103" manufactured by AS ONE Corporation.

[0025] In the above sealant, the solubility of the poorly water-soluble salt in water at 20°C is 1.0 x 10 -3From the viewpoint of further enhancing the waterproofing of the sealed area and its surroundings, the solubility of the poorly water-soluble salt in water at 20°C is preferably 8.0 × 10 -4 mol / L or less, more preferably 5.0 × 10 -4 mol / L or less, more preferably 2.0 × 10 -4 The lower limit of the solubility of the poorly water-soluble salt in water at 20°C is not particularly limited. The solubility of the poorly water-soluble salt in water at 20°C is 1.0 × 10 -10 mol / L or more, and may be 1.0 × 10 -9 It may be mol / L or more.

[0026] The solubility of the above-mentioned poorly water-soluble salt in water at 20°C can be measured by the following method. 10 g of the poorly water-soluble salt is added to 100 g of pure water, and the mixture is stirred at 20°C for 10 minutes. Then, 10 g of the solution is placed in an evaporating dish, and the water is completely removed at 100°C. The solubility of the above-mentioned poorly water-soluble salt in water at 20°C is calculated from the weight of the poorly water-soluble salt remaining on the evaporating dish.

[0027] The viscosity (η23) of the sealant at 23°C is preferably 500 mPa·s or more, more preferably 10,000 mPa·s or more, and preferably 2,000,000 mPa·s or less, more preferably 1,000,000 mPa·s or less. When the viscosity (η23) is equal to or greater than the lower limit and equal to or less than the upper limit, the sealant can be easily filled (injected), improving workability. The viscosity (η23) can be adjusted appropriately by changing the types and amounts of the ingredients.

[0028] The viscosity (η23) can be measured, for example, using a Brookfield viscometer (VISCOSTAR manufactured by FUNGILAB) under conditions of 23° C. and 20 rpm.

[0029] Furthermore, the sealant according to the present invention can be used whether the area to be sealed is dry or wet. Furthermore, the sealant according to the present invention can be used even when water is leaking from the area to be sealed. Therefore, the sealant according to the present invention can preserve structures for a variety of applications.

[0030] The structure is not particularly limited. Examples of the structure include concrete structures. Examples of the concrete structure include buildings, underground tunnels, undersea tunnels, mountain tunnels, and insulators (grout portions) arranged on the outer surfaces of pipes, etc. From the viewpoint of more effectively exerting the effects of the present invention, the structure is preferably a concrete structure. The structure may also be an underground structure.

[0031] The sealant of the present invention is preferably used for gaps (gaps) in structures. The sealant of the present invention is preferably used for cracks or fissures in structures. The sealant of the present invention is preferably used for gaps (joints) at joints between members in structures. The sealant of the present invention is also preferably used at the boundary between a structure and the ground behind the structure. Furthermore, the sealant of the present invention is preferably used as a sheath material. Specifically, the sealant of the present invention is preferably used as a sheath material for insulators (grout portions) arranged on the outer surfaces of anchors, cables, pipes, etc. The sealant of the present invention is preferably used to protect the outer surfaces of insulators arranged on the outer surfaces of anchors, cables, pipes, etc.

[0032] Furthermore, at final waste disposal sites, waterproof sheets are sometimes installed at the boundary between concrete structures and the ground. Furthermore, in the NATM method, which is one of the tunnel excavation methods, waterproof sheets are sometimes installed at the boundary between the tunnel (lining concrete) and the ground behind the tunnel. The sealant of the present invention is suitable for use as a material for the waterproof sheets.

[0033] From the viewpoint of more effectively achieving the effects of the present invention, it is preferable that the sealant is a sealant for an object to be sealed, including concrete. From the viewpoint of more effectively achieving the effects of the present invention, it is preferable that the sealant is a sealant for a concrete structure. From the viewpoint of more effectively achieving the effects of the present invention, it is preferable that the sealant is placed in a portion to be sealed of an object to be sealed, including concrete. The sealant may be a sealant for an object to be sealed, including ground and concrete. The sealant may be placed in a portion to be sealed of an object to be sealed, including ground and concrete.

[0034] The components used in the sealant according to the present invention will be described in detail below.

[0035] <Resin> The sealing material includes a resin.

[0036] Examples of the resin include thermoplastic resins and curable resins. From the viewpoint of easily molding the sealant by extrusion molding or injection molding, the resin preferably contains a thermoplastic resin. From the viewpoint of effectively sealing the target part by injecting or applying the sealant, the resin preferably contains a curable resin. Only one type of the resin may be used, or two or more types may be used in combination.

[0037] Examples of the thermoplastic resin include fluororesin, polyolefin resin, polyvinyl chloride resin, polyamide resin, polycarbonate resin, polystyrene resin, polyester resin, acrylonitrile-butadiene-styrene resin (ABS resin), polyethylene terephthalate (PET), and polymethyl methacrylate (PMMA).

[0038] Examples of the polyolefin resin include polyethylene, polypropylene, ethylene-propylene copolymer (EPDM), isobutylene-isoprene copolymer, polystyrene, polybutene, polyisobutylene, polybutadiene, acrylonitrile-butadiene copolymer, ethylene-vinyl acetate copolymer, and ethylene-α-olefin copolymer.

[0039] Examples of the curable resin include modified silicone resin, silicone resin, epoxy resin, acrylic resin, unsaturated polyester resin, polyurea resin, urethane resin, phenol resin, vinyl ester resin, naphthoxazine resin, etc. The curable resin may be used alone or in combination of two or more.

[0040] The curable resin may be a one-component curable resin or a two-component curable resin. Examples of the one-component curable resin include a thermosetting resin, a photocurable resin, and a moisture-curable resin. The two-component curable resin is used in combination with a curing agent. From the viewpoint of improving workability on site, the curable resin preferably contains a moisture-curable resin, and is preferably a moisture-curable resin. The curable resin may be used in combination with a curing agent, or may not be used in combination with a curing agent.

[0041] From the viewpoint of increasing elasticity, the curable resin preferably contains a modified silicone resin, and is preferably a modified silicone resin.

[0042] From the viewpoint of improving workability on site, the modified silicone resin is preferably a moisture-curable modified silicone resin. The moisture-curable modified silicone resin has a hydrolyzable silicon group. The modified silicone resin having a hydrolyzable silicon group has a polyether polymer, a polyolefin polymer, or an acrylic polymer as the main chain (the portion excluding the hydrolyzable silicon group). Therefore, examples of monomers that form the main chain include alkylene oxide monomers, olefin monomers, and acrylic monomers. The polymer may be a homopolymer or a copolymer. When the polymer is a copolymer, examples of the monomers used include alkylene oxide monomers, olefin monomer components, acrylic monomers, and vinyl monomers. Only one type of modified silicone resin may be used, or two or more types may be used in combination.

[0043] Examples of the alkylene oxide monomer include ethylene oxide, propylene oxide, butylene oxide, etc. From the viewpoint of improving the elongation and viscous handleability after curing, the alkylene oxide monomer is preferably polypropylene oxide obtained by polymerizing propylene oxide.

[0044] Examples of the olefin-based monomer include isobutylene.

[0045] Examples of the acrylic monomer include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, tert-butyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, isomyristyl (meth)acrylate, stearyl (meth)acrylate, and isobornyl (meth)acrylate. acrylate, benzyl (meth)acrylate, 2-butoxyethyl (meth)acrylate, 2-phenoxyethyl (meth)acrylate, glycidyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, hexanediol di(meth)acrylate, ethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, Dimethylolpropane tri(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, epoxy acrylate, polyester acrylate, urethane acrylate, 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate ) acrylate, 2-hydroxybutyl (meth)acrylate, 5-hydroxypentyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 3-hydroxy-3-methylbutyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, pentaerythritol tri(meth)acrylate, 2-[(meth)acryloyloxy]ethyl 2-hydroxyethyl phthalate, 2-[(meth)acryloyloxy]ethyl 2-hydroxypropyl phthalate, and the like.When the acrylic polymer is one in which other vinyl monomer components have been copolymerized, a hydrolyzable silicon group can be introduced by copolymerizing a vinyl monomer component having a hydrolyzable silicon group.

[0046] From the viewpoint of improving weather resistance, the main chain of the modified silicone resin preferably has a structural unit derived from an acrylic monomer.

[0047] From the viewpoint of improving weather resistance, the content of structural units derived from acrylic monomers in 100% by weight of the main chain in the modified silicone resin is preferably 5% by weight or more, and preferably 20% by weight or less.

[0048] The hydrolyzable silicon group is not particularly limited, but examples thereof include halogenated silyl groups, alkenyloxysilyl groups, acyloxysilyl groups, aminosilyl groups, aminooxysilyl groups, oximesilyl groups, amidosilyl groups, and alkoxysilyl groups.

[0049] The number of hydrolyzable groups bonded to a silicon atom in the hydrolyzable silicon group is preferably 1 or more, and preferably 3 or less. One or more types of hydrolyzable groups may be bonded to one silicon atom. The hydrolyzable group and a non-hydrolyzable group may be bonded to one silicon atom. Due to their excellent stability and ease of handling, the hydrolyzable silicon group is preferably a monoalkoxysilyl group, a dialkoxysilyl group, or a trialkoxysilyl group.

[0050] When the curable resin contains the modified silicone resin, the curable resin preferably contains a silanol condensation catalyst. The curable resin preferably contains the modified silicone resin and a silanol condensation catalyst. By using the silanol condensation catalyst, the modified silicone resin can be cured in a short time. The silanol condensation catalyst may be used alone or in combination of two or more.

[0051] Examples of the silanol condensation catalyst include tin catalysts such as monoalkyltin esters and dialkyltin esters, poly(dialkylstannoxane) disilicate resins, and organic titanates.

[0052] Examples of the monoalkyltin esters include butyltin tris(2-ethylhexanoate), etc. Examples of the dialkyltin esters include dibutyltin acetate, dibutyltin dilaurate, dibutyltin dioctoate, dibutyltin dioleate, dibutyltin dimethoxide, dibutyltin diphenoxide, dibutyltin diacetylacetonate, dibutyltin acetoacetate, and stannous octoate.

[0053] Examples of the organic titanate include titanium alkoxides such as tetrabutyl titanate, tetraisopropyl titanate, tetramethyl titanate, and tetra(2-ethylhexyl titanate)triethanolamine titanate; and titanium chelates such as titanium tetraacetylacetonate, titanium ethylacetoacetate, and octylene glycolate.

[0054] The content of the silicone condensation catalyst is preferably 0.1 parts by weight or more, more preferably 1 part by weight or more, preferably 10 parts by weight or less, more preferably 5 parts by weight or less, relative to 100 parts by weight of the modified silicone resin.When the content of the silicone condensation catalyst is above the lower limit, the material of the resin layer containing the modified silicone resin can be cured in a short time, and the resin layer can be obtained well in a short time.When the content of the silicone condensation catalyst is below the upper limit, the adhesive strength of the resin layer can be increased.

[0055] Examples of the silicone resin include organopolysiloxanes having two or more alkenyl groups bonded to silicon atoms. The main chain of the organopolysiloxane is generally a diorganosiloxane polymer, but it may have a partially branched or cyclic structure. Examples of the alkenyl group contained in the organopolysiloxane include vinyl, 1-propenyl, 2-propenyl, isopropenyl, butenyl, 1-methyl-2-propenyl, petenyl, hexenyl, octenyl, and cyclohexenyl groups.

[0056] Examples of the curing agent (crosslinking agent) for the silicone resin include organohydrogenpolysiloxane having two or more SiH groups. Examples of the organohydrogenpolysiloxane include phenylmethylhydrogenpolysiloxane, 1,1,3,3-tetramethyldisiloxane, 1,3,5,7-tetramethylcyclotetrasiloxane, methylhydrogenpolysiloxane capped at both ends with trimethylsiloxy groups, dimethylsiloxane-methylhydrogensiloxane copolymer capped at both ends with trimethylsiloxy groups, dimethylpolysiloxane capped at both ends with dimethylhydrogensiloxy groups, dimethylsiloxane-methylhydrogensiloxane copolymer capped at both ends with dimethylhydrogensiloxy groups, methylhydrogensiloxane-diphenylsiloxane copolymer capped at both ends with trimethylsiloxy groups, and methylhydrogensiloxane-diphenylsiloxane-dimethylsiloxane copolymer capped at both ends with trimethylsiloxy groups.

[0057] Examples of the epoxy resin include bisphenol-type epoxy resins such as bisphenol A-type epoxy resins, bisphenol F-type epoxy resins, bisphenol S-type epoxy resins, and hydrogenated versions of these; glycidyl ether-type epoxy resins such as polypropylene glycol diglycidyl ether-type epoxy resins; ester-type epoxy resins such as phthalic acid diglycidyl ester-type epoxy resins; novolac-type epoxy resins such as phenol novolac-type epoxy resins, bisphenol A novolac-type epoxy resins, cresol novolac-type epoxy resins, and hydrogenated versions of these; trisphenol-type multifunctional epoxy resins such as triphenolmethane-type epoxy resins; triglycidyl isopropyl Examples include nitrogen-containing ring-type polyfunctional epoxy resins such as cyanurate-type epoxy resins, tetraglycidyldiaminodiphenylmethane-type epoxy resins, tetraglycidylmeta-xylenediamine-type epoxy resins, and hydantoin-type epoxy resins; condensed-ring epoxy resins such as naphthalene-type epoxy resins; biphenyl-type epoxy resins; dicyclopentadiene-type epoxy resins; ether ester-type epoxy resins; epoxy resins having an alicyclic structure such as 3,4-epoxycyclohexylmethyl-3',4'-epoxycyclohexanecarboxylate; urethane-type epoxy resins; and rubber-modified epoxy resins having a rubber skeleton such as polybutadiene and acrylonitrile butadiene rubber (NBR).

[0058] When the curable resin contains the epoxy resin, the curable resin preferably contains a curing agent for the epoxy resin (epoxy curing agent). That is, the curable component preferably contains the epoxy resin and the epoxy curing agent.

[0059] Examples of the epoxy resin curing agent (epoxy curing agent) include amine compounds, imidazole compounds, amide compounds, and cyano compounds. Examples of the amine compounds include ethylenediamine, propylenediamine, diethylenetriamine, triethylenetetramine, their amine adducts, metaphenylenediamine, diaminodiphenylmethane, and diaminodiphenylsulfone. Examples of the imidazole compounds include methylimidazole, 2-ethyl-4-methylimidazole, 1-isobutyl-2-methylimidazole, 1-benzyl-2-methylimidazole, 2-ethyl-4-methylimidazole, ethylimidazole, isopropylimidazole, 2,4-dimethylimidazole, phenylimidazole, undecylimidazole, heptadecylimidazole, 2-phenyl-4-methylimidazole, 2-phenyl-4,5-dihydroxymethylimidazole, and 2-phenyl-4-methyl-5-hydroxymethylimidazole. Examples of the amide compounds include polyamides, etc. Examples of the cyano compounds include dicyandiamide, etc.

[0060] The epoxy resin may be a latent curing agent such as ketimine, in which the active amine is blocked and which becomes active under certain conditions such as moisture. For example, ketimine is stable in the absence of moisture, but generally becomes a primary amine in the presence of moisture and reacts with the epoxy resin. Specific examples include 2,5,8-triaza-1,8-nonadiene, 2,10-dimethyl-3,6,9-triaza-2,9-undecadiene, 2,10-diphenyl-3,6,9-triaza-2,9-undecadiene, 3,11-dimethyl-4,7,10-triaza-3,10-tridecadiene, 3,11-diethyl-4,7,10-triaza-3,10-tridecadiene, 2,4,12,14-tetramethyl-5,8,11-triaza-4,11-pentadecadiene, 2,4,20,22-tetramethyl-5,12,19-triaza-4,19-trieicosadiene, and 2,4,15,17-tetramethyl-5,8,11,14-tetraaza-4,14-octadecadiene.

[0061] A cured product of the epoxy resin can be obtained by reacting the epoxy resin with the epoxy curing agent.

[0062] From the viewpoint of more effectively exerting the effects of the present invention, the epoxy resin preferably contains an epoxy resin having an aromatic skeleton, and is more preferably a bisphenol A type epoxy resin or a bisphenol F type epoxy resin.

[0063] From the viewpoint of more effectively exerting the effects of the present invention, the epoxy curing agent is preferably an amine-based curing agent (amine compound).

[0064] A urethane resin can be obtained by curing a polyol compound with an isocyanate compound. Examples of the polyol compound include bisphenol A, bisphenol F, phenol novolac, cresol novolac, cyclohexanediol, methylcyclohexanediol, isophoronediol, dicyclohexylmethanediol, dimethyldicyclohexylmethanediol, ethylene glycol, propylene glycol, butanediol, pentanediol, hexanediol, polyester polyol, polyether polyol, a polymer obtained by dehydration condensation of a polybasic acid and a polyhydric alcohol, and a polymer obtained by ring-opening polymerization of a lactone such as ε-caprolactone or α-methyl-ε-caprolactone.

[0065] The isocyanate compound may be a polyisocyanate compound. Examples of the polyisocyanate compound include aromatic polyisocyanates, alicyclic polyisocyanates, and aliphatic polyisocyanates. Examples of the aromatic polyisocyanates include phenylene diisocyanate, toluene diisocyanate, tolylene diisocyanate, xylylene diisocyanate, diphenylmethane diisocyanate, dimethyldiphenylmethane diisocyanate, triphenylmethane triisocyanate, naphthalene diisocyanate, and polymethylene polyphenyl polyisocyanate. Examples of the alicyclic polyisocyanates include cyclohexylene diisocyanate, methylcyclohexylene diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, and dimethyldicyclohexylmethane diisocyanate. Examples of the aliphatic polyisocyanate include methylene diisocyanate, ethylene diisocyanate, propylene diisocyanate, tetramethylene diisocyanate, and hexamethylene diisocyanate.

[0066] From the viewpoint of more effectively exerting the effects of the present invention, the polyol compound is preferably a polyester polyol or a polyether polyol, and from the viewpoint of more effectively exerting the effects of the present invention, the curing agent (isocyanate compound) for the polyol compound is preferably diphenylmethane diisocyanate or toluene diisocyanate.

[0067] The compounding ratio of the polyol compound and the polyisocyanate compound can be appropriately changed depending on the combination of the types of polyol compound and polyisocyanate compound. The compounding amount of the polyisocyanate compound is preferably an amount such that the amount of hydroxyl groups in the polyol compound is equal to the amount of isocyanate groups (NCO amount) in the polyisocyanate compound.

[0068] Examples of the phenol resin include novolac type phenol, biphenol type phenol, naphthalene type phenol, dicyclopentadiene type phenol, aralkyl type phenol, and dicyclopentadiene type phenol.

[0069] Examples of the curing agent for the phenolic resin include hexamethylenetetramine and paraformaldehyde.

[0070] Examples of the vinyl ester resin include a reaction product of an epoxy resin with an unsaturated monobasic acid. Examples of the epoxy resin include aliphatic glycidyl ethers such as bisphenol A diglycidyl ether and its high molecular weight homologues, novolac polyglycidyl ether and its high molecular weight homologues, and 1,6-hexanediol diglycidyl ether. Examples of the unsaturated monobasic acid include acrylic acid and methacrylic acid. Examples of the reaction product of the epoxy resin with the acrylic acid and methacrylic acid include epoxy (meth)acrylate.

[0071] Examples of the curing agent for the vinyl ester resin include organic peroxides, such as ketone peroxides, perbenzoates, hydroperoxides, diacyl peroxides, peroxyketals, hydroperoxides, diallyl peroxides, peroxyesters, and peroxydicarbonates.

[0072] When the curable resin contains the vinyl ester resin, the curable component may contain a radically polymerizable unsaturated monomer. Examples of the radically polymerizable unsaturated monomer include styrene monomer, α-, o-, m-, p-alkyl, nitro, cyano, amide, and ester derivatives of styrene, styrene-based monomers such as chlorostyrene, vinyltoluene, and divinylbenzene, dienes such as butadiene, 2,3-dimethylbutadiene, isoprene, and chloroprene; ethyl (meth)acrylate, methyl (meth)acrylate, n-propyl (meth)acrylate, i-propyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, dodecyl (meth)acrylate, and (meth)acrylate. (meth)acrylic acid esters such as cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, tetrahydrofuryl (meth)acrylate, acetoacetoxyethyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, and phenoxyethyl (meth)acrylate; (meth)acrylic acid amides such as (meth)acrylic acid amide and (meth)acrylic acid N,N-dimethylamide; vinyl resins such as (meth)acrylic acid anilide; unsaturated dicarboxylic acid diesters such as diethyl citraconic acid; monomaleimide resins such as N-phenylmaleimide; and N-(meth)acryloylphthalimide.

[0073] The content of the resin in 100% by weight of the sealant is preferably 30% by weight or more, more preferably 50% by weight or more, even more preferably 55% by weight or more, particularly preferably 60% by weight or more, and preferably 97% by weight or less, more preferably 95% by weight or less, even more preferably 90% by weight or less, particularly preferably 80% by weight or less. When the content of the resin is above the lower limit and below the upper limit, cations or anions are released more effectively, and poorly water-soluble salts are produced well. As a result, the sealed area and its surroundings are further densified, and the structure can be maintained in a stable state for a longer period of time.

[0074] The content of the thermoplastic resin in 100% by weight of the sealant is preferably 40% by weight or more, more preferably 50% by weight or more, even more preferably 60% by weight or more, particularly preferably 65% ​​by weight or more, and preferably 97% by weight or less, more preferably 95% by weight or less, even more preferably 90% by weight or less, particularly preferably 85% by weight or less. When the content of the thermoplastic resin is above the above lower limit and below the above upper limit, cations or anions are released more effectively, and poorly water-soluble salts are produced well. As a result, the sealed area and its surroundings are further densified, and the structure can be maintained in a stable state for a longer period of time.

[0075] The content of the curable resin in 100% by weight of the sealant is preferably 30% by weight or more, more preferably 50% by weight or more, even more preferably 55% by weight or more, particularly preferably 60% by weight or more, and preferably 97% by weight or less, more preferably 95% by weight or less, even more preferably 90% by weight or less, particularly preferably 80% by weight or less. When the content of the curable resin is above the lower limit and below the upper limit, cations or anions are released more effectively, and poorly water-soluble salts are produced well. As a result, the sealed area and its surroundings are further densified, and the structure can be maintained in a stable state for a longer period of time.

[0076] The content of the moisture-curing resin in 100% by weight of the sealant is preferably 35% by weight or more, more preferably 50% by weight or more, even more preferably 55% by weight or more, particularly preferably 60% by weight or more, and preferably 95% by weight or less, more preferably 90% by weight or less, even more preferably 85% by weight or less, particularly preferably 80% by weight or less. When the content of the moisture-curing resin is above the lower limit and below the upper limit, cations or anions are released more effectively, and poorly water-soluble salts are produced well. As a result, the sealed area and its surroundings are further densified, and the structure can be maintained in a stable state for a longer period of time.

[0077] The content of the modified silicone resin in 100% by weight of the sealant is preferably 35% by weight or more, more preferably 50% by weight or more, even more preferably 55% by weight or more, particularly preferably 60% by weight or more, and preferably 97% by weight or less, more preferably 95% by weight or less, even more preferably 90% by weight or less, particularly preferably 80% by weight or less. When the content of the modified silicone resin is above the above lower limit and below the above upper limit, cations or anions are released more effectively, and poorly water-soluble salts are produced well. As a result, the sealed area and its surroundings are further densified, and the structure can be maintained in a stable state for a longer period of time.

[0078] <Ion-releasing compounds> The sealing material contains an ion-releasing compound capable of releasing cations or anions (ion-releasing compound), which is capable of generating a poorly water-soluble salt.

[0079] The ion-releasing compound may be a compound capable of releasing a cation, a compound capable of releasing an anion, a compound capable of releasing both a cation and an anion, or a mixture of a compound capable of releasing a cation and a compound capable of releasing an anion. The ion-releasing compound may contain a compound capable of releasing a cation, a compound capable of releasing an anion, or a compound capable of releasing a cation and a compound capable of releasing an anion. Only one type of the ion-releasing compound may be used, or two or more types may be used in combination.

[0080] The ion-releasing compound preferably generates a poorly water-soluble salt upon contact with moisture or the like attached to the ground or a structure. Preferably, the ion-releasing compound releases cations or anions when water or moisture reaches the location where the sealant is placed. Specifically, if the ion-releasing compound is a compound capable of releasing cations, the cations released from the ion-releasing compound preferably react with anions dissolved in moisture or the like to form a poorly water-soluble salt. If the ion-releasing compound is a compound capable of releasing anions, the anions released from the ion-releasing compound preferably react with cations dissolved in moisture or the like to form a poorly water-soluble salt. Furthermore, if the ion-releasing compound is a compound capable of releasing both cations and anions, or a mixture of a compound capable of releasing cations and a compound capable of releasing anions, the cations and anions released from the ion-releasing compound preferably migrate to a medium such as moisture and form a poorly water-soluble salt at the point where they meet.

[0081] The ion-releasing compound may be an inorganic salt, an ion-exchange resin, or an ion complex.

[0082] Examples of the ion-releasing compound include calcium silicate, tricalcium silicate, dicalcium silicate, calcium aluminate, calcium aluminoferrite, calcium hydroxide, calcium oxide, calcium acetate, calcium lactate, barium lactate, calcium sulfate, calcium chloride, calcium nitrate, calcium bicarbonate, sodium hydrogen phosphate, potassium carbonate, potassium bicarbonate, ammonium carbonate, ammonium bicarbonate, sodium carbonate, and sodium bicarbonate. The ion-releasing compound is preferably one of these ion-releasing compounds. These ion-releasing compounds can more effectively produce poorly water-soluble salts.

[0083] Examples of the compound capable of releasing cations include calcium silicate, tricalcium silicate, dicalcium silicate, calcium aluminate, calcium aluminoferrite, calcium hydroxide, calcium oxide, calcium acetate, calcium lactate, barium lactate, calcium sulfate, calcium chloride, calcium nitrate, calcium bicarbonate, etc. The compound capable of releasing cations may be used alone or in combination of two or more.

[0084] The compound capable of releasing cations is preferably calcium silicate, tricalcium silicate, dicalcium silicate, calcium aluminate, calcium aluminoferrite, calcium hydroxide, calcium oxide, calcium acetate, calcium lactate, barium lactate, calcium sulfate, calcium chloride, calcium nitrate, or calcium bicarbonate. When the compound capable of releasing cations is one of the preferred compounds, the effects of the present invention can be more effectively achieved. From the viewpoint of more effectively achieving the effects of the present invention, the compound capable of releasing cations is more preferably calcium oxide, calcium chloride, calcium nitrate, calcium acetate, calcium lactate, or barium lactate, and even more preferably calcium lactate. From the viewpoint of more effectively achieving the effects of the present invention, the compound capable of releasing cations is preferably a compound capable of releasing calcium ions, and more preferably an organic acid calcium salt. Examples of the organic acid calcium salt include calcium acetate and calcium lactate.

[0085] Examples of the compound capable of releasing anions include sodium hydrogen phosphate, potassium carbonate, potassium hydrogen carbonate, ammonium carbonate, ammonium hydrogen carbonate, sodium carbonate, sodium hydrogen carbonate, calcium hydrogen carbonate, etc. The compound capable of releasing anions may be used alone or in combination of two or more.

[0086] From the viewpoint of more effectively exerting the effects of the present invention, the compound capable of releasing anions is preferably sodium hydrogen phosphate, potassium carbonate, potassium hydrogen carbonate, ammonium carbonate, ammonium hydrogen carbonate, sodium carbonate, sodium hydrogen carbonate, or calcium hydrogen carbonate. From the viewpoint of more effectively exerting the effects of the present invention, the compound capable of releasing anions is more preferably sodium hydrogen phosphate, sodium carbonate, or sodium hydrogen carbonate, and even more preferably sodium hydrogen carbonate. From the viewpoint of more effectively exerting the effects of the present invention, the compound capable of releasing anions is preferably a compound capable of releasing hydrogen carbonate ions (bicarbonate ions) or carbonate ions.

[0087] Examples of the compound capable of releasing both cations and anions include calcium bicarbonate.

[0088] From the viewpoint of producing the poorly water-soluble salt more efficiently, the sealant is preferably a mixture of a compound capable of releasing cations and a compound capable of releasing anions, and more preferably a mixture of a compound capable of releasing calcium ions and a compound capable of releasing bicarbonate ions or carbonate ions. From the viewpoint of producing the poorly water-soluble salt more efficiently, the sealant preferably contains a compound capable of releasing cations and a compound capable of releasing anions, and more preferably contains a compound capable of releasing calcium ions and a compound capable of releasing bicarbonate ions or carbonate ions.

[0089] Examples of the poorly water-soluble salt include the following compounds: calcium carbonate (specific gravity: 2.71, solubility in water at 20°C: 1.5 x 10 -4 mol / L). Barium carbonate (specific gravity: 4.29, solubility in water at 20°C: 1.25 x 10 -4 mol / L). Calcium phosphate (specific gravity: 3.14, solubility in water at 20°C: 6.5 x 10 -5 mol / L). Iron hydroxide (specific gravity: 3.40, solubility in water at 20°C: 5.0 x 10 -6 mol / L).

[0090] From the viewpoint of more effectively exerting the effects of the present invention, the poorly water-soluble salt is preferably calcium carbonate, barium carbonate, calcium phosphate, or iron hydroxide. From the viewpoint of more effectively exerting the effects of the present invention, the ion-releasing compound is preferably capable of generating calcium carbonate, barium carbonate, calcium phosphate, or iron hydroxide as the poorly water-soluble salt. From the viewpoint of more effectively exerting the effects of the present invention, the poorly water-soluble salt is preferably calcium carbonate. From the viewpoint of more effectively exerting the effects of the present invention, the ion-releasing compound is preferably capable of generating calcium carbonate as the poorly water-soluble salt.

[0091] The ion-releasing compound may be particulate. The ion-releasing compound may be spherical, may have a shape other than spherical, or may be flat. The ion-releasing compound is preferably spherical.

[0092] The particle diameter of the ion-releasing compound is preferably 1.0 μm or more, more preferably 5.0 μm or more, even more preferably 10 μm or more, and preferably 1000 μm or less, more preferably 500 μm or less, even more preferably 150 μm or less, and particularly preferably 100 μm or less. When the particle diameter of the ion-releasing compound is equal to or greater than the above-mentioned lower limit, the ion-releasing compound is well coated with the coating agent described below, thereby improving the dispersibility of the ion-releasing compound in the sealant and the sealed product. Furthermore, when the particle diameter of the ion-releasing compound is equal to or greater than the above-mentioned lower limit, the viscosity of the sealant when filling the sealant into the sealed area is improved, thereby improving the placement of the sealant. When the particle diameter of the ion-releasing compound is equal to or less than the above-mentioned upper limit, the dispersibility of the ion-releasing compound in the sealant and the sealed product is improved.

[0093] The particle size of the ion-releasing compound is preferably an average particle size. The average particle size indicates a number-average particle size. The average particle size of the ion-releasing compound is determined by observing 50 random ion-releasing compounds with an electron microscope or an optical microscope and calculating the average value.

[0094] In the sealant, the surface of the ion-releasing compound may be coated with a coating agent. The ion-releasing compound may be an inclusion of a microcapsule. When the ion-releasing compound is an inorganic salt, the surface of the ion-releasing compound in the sealant is preferably coated with a coating agent. When the ion-releasing compound is an inorganic salt, the sealant preferably contains microcapsules containing the ion-releasing compound as an inclusion. When the surface of the ion-releasing compound is coated with a coating agent or the ion-releasing compound is an inclusion of a microcapsule, the timing and amount of release of cations or anions from the ion-releasing compound can be controlled.

[0095] The ion-releasing compound coated with the coating agent is preferably capable of releasing cations or anions when moisture such as water or humidity comes into contact with the sealant (or sealed object) and the moisture diffuses and penetrates into the coating agent. The ion-releasing compound coated with the coating agent may be capable of releasing cations or anions from voids in the coating agent. The ion-releasing compound coated with the coating agent may be capable of diffusing into the coating agent and releasing cations or anions. In these cases, the timing and amount of cations or anions released from the ion-releasing compound can be more effectively controlled.

[0096] The microcapsules are preferably capable of releasing the ion-releasing compound. The membranes constituting the microcapsules preferably disintegrate upon contact with water or moisture, allowing for better control of the timing and amount of release of cations or anions from the ion-releasing compound.

[0097] The material of the membrane constituting the microcapsules and the material of the coating agent for coating the surface of the ion-releasing compound can be appropriately selected depending on the type of the ion-releasing compound. The material of the membrane constituting the microcapsules and the material of the coating agent for coating the surface of the ion-releasing compound preferably contain a coupling agent or a resin. In this case, the dispersibility of the ion-releasing compound in the sealant and the sealed object can be improved, and the timing and amount of release of cations or anions can be well controlled. Furthermore, the thickness of the membrane constituting the microcapsules can be made uniform, and the surface of the ion-releasing compound can be uniformly coated with the coating agent.

[0098] Examples of the coupling agent include a silane coupling agent and a titanium coupling agent.

[0099] Examples of the resin include water-soluble resins, thermoplastic resins, and curable resins. Only one type of resin may be used, or two or more types may be used in combination. The resin contained in the sealant and the resin contained in the material of the coating agent may be the same or different.

[0100] Examples of the water-soluble resin include polyvinyl alcohol, polylactic acid resin (PLA resin), poly(meth)acrylic acid, poly(meth)acrylamide, polyvinylpyrrolidone, polyethylene oxide, and methylcellulose.

[0101] Examples of the thermoplastic resin and the curable resin include the thermoplastic resins and curable resins described above.

[0102] From the viewpoint of better controlling the timing and amount of release of cations or anions from the ion-releasing compound, the resin contained in the material of the coating agent preferably contains a thermoplastic resin, more preferably contains a polyolefin resin, even more preferably contains an ethylene-vinyl acetate copolymer, and is particularly preferably an ethylene-vinyl acetate copolymer.

[0103] The thickness of the membrane constituting the microcapsules and the thickness of the coating layer of the coating agent are not particularly limited. From the viewpoint of better controlling the timing and amount of release of cations or anions from the ion-releasing compound, the thickness of the membrane constituting the microcapsules and the thickness of the coating layer of the coating agent are preferably 1 μm or more, more preferably 5 μm or more, and preferably 1000 μm or less, more preferably 200 μm or less.

[0104] The content of the ion-releasing compound in 100% by weight of the sealant is preferably 3% by weight or more, more preferably 5% by weight or more, even more preferably 10% by weight or more, particularly preferably 20% by weight or more, and preferably 70% by weight or less, more preferably 50% by weight or less, even more preferably 45% by weight or less, particularly preferably 40% by weight or less. When the content of the ion-releasing compound is above the above-mentioned lower limit and below the above-mentioned upper limit, cations or anions are released more effectively, and poorly water-soluble salts are efficiently produced. As a result, the sealed area and its surroundings are further densified, and the structure can be maintained in a stable state for a longer period of time. When the content of the ion-releasing compound is below the above-mentioned upper limit, the appearance of the structure after sealing with the sealant can be improved, and the strength of the sealed area and its surroundings can be increased.

[0105] The content of the ion-releasing compound is preferably 3 parts by weight or more, more preferably 5 parts by weight or more, even more preferably 10 parts by weight or more, particularly preferably 20 parts by weight or more, and preferably 200 parts by weight or less, more preferably 100 parts by weight or less, and even more preferably 70 parts by weight or less, per 100 parts by weight of the resin. When the content of the ion-releasing compound is above the lower limit and below the upper limit, cations or anions are released more effectively, and poorly water-soluble salts are produced efficiently. As a result, the sealed area and its surroundings are further densified, allowing the structure to be maintained in a stable state for a longer period of time. When the content of the ion-releasing compound is below the upper limit, the viscosity of the sealant when filling the area to be sealed is improved, thereby improving the placement of the sealant.

[0106] The total content of the ion-releasing compound and the coating agent in 100% by weight of the sealant is preferably 3% by weight or more, more preferably 5% by weight or more, and preferably 70% by weight or less, more preferably 50% by weight or less. When the total content of the ion-releasing compound and the coating agent is above the lower limit and below the upper limit, cations or anions are released more effectively, and poorly water-soluble salts are produced efficiently. As a result, the sealed area and its surroundings are further densified, allowing the structure to be maintained in a stable state for a longer period of time. When the total content of the ion-releasing compound and the coating agent is below the upper limit, the viscosity of the sealant when filling the area to be sealed is improved, thereby improving the placement of the sealant.

[0107] <Other ingredients> The sealant may contain other components in addition to the resin, the ion-releasing compound, and the coating agent, as necessary, such as a reaction catalyst, a reaction accelerator, a crosslinking agent, a water-absorbing agent, a foam stabilizer, an antioxidant, and a colorant.

[0108] (Structure and method for manufacturing the structure) A structure can be obtained using the sealant according to the present invention. The structure preferably comprises an object to be sealed having a portion to be sealed, and a sealant disposed on the portion to be sealed. The sealant is preferably formed from the sealant. The sealant may be formed by curing a resin (curable resin) in the sealant. The sealant may be a cured product of the sealant. The sealant may be formed by extrusion molding or injection molding the sealant. The sealant may be a molded product of the sealant.

[0109] The ion-releasing compound in the sealant (in the cured product of the sealant or in the molded product of the sealant) is preferably dispersed in the resin or in the cured product of the curable resin.

[0110] The sealing material may be a waterproof sheet or a waterproof member. The sealing material may be in the form of a sheet. When the sealing material is in the form of a sheet, the thickness of the sealing material is preferably 0.05 mm or more, more preferably 0.1 mm or more, even more preferably 0.5 mm or more, and preferably 5 mm or less, more preferably 3 mm or less, even more preferably 2 mm or less. When the thickness of the sealing material is equal to or greater than the above-mentioned lower limit and equal to or less than the above-mentioned upper limit, the waterproofness of the sealed area and its surroundings can be improved.

[0111] The method for manufacturing the structure preferably comprises (1A) a disposing step of disposing the sealant on the portion to be sealed of the object to be sealed, and (2A) a curing step of curing the resin in the sealant. The method for manufacturing the structure may also comprise (1B) a molding step of extrusion molding or injection molding the sealant to form a sealed object, and (2B) a disposing step of disposing the sealant on the portion to be sealed of the object to be sealed.

[0112] The method for manufacturing the structure described above provides a structure having a sealing material disposed in the sealing target portion, and the structure can be densified in the sealed area and its surroundings, and can be maintained in a stable state for a long period of time.

[0113] From the viewpoint of more effectively achieving the effects of the present invention, it is preferable that the object to be sealed includes concrete. From the viewpoint of more effectively achieving the effects of the present invention, it is preferable that the object to be sealed is a concrete structure. The object to be sealed may include the ground. The part to be sealed may be a void or the outer surface of the object to be sealed. It is preferable that the part to be sealed is a void in the concrete structure or the outer surface of the concrete structure. The void in the concrete structure may be a crack in the concrete structure, a gap at a joint between members in the concrete structure, or a boundary between the concrete structure and the ground. Examples of the outer surface of the concrete structure include the outer surface of an insulator (grout portion) arranged on the outer surface of a pipe or the like.

[0114] The sealant may be used by filling the area to be sealed. There is no particular limitation on the method for filling the area to be sealed with the sealant. Examples of methods for filling the area to be sealed with the sealant include forming an injection port in the structure that penetrates from the front to the back of the structure, and injecting the sealant into the area to be sealed through the injection port. The amount of the sealant injected can be changed as appropriate depending on the size of the area to be filled (the area to be sealed), etc. The sealant may be filled by a backfilling method.

[0115] The pressure when filling (injecting) the sealant can be changed as appropriate depending on the viscosity of the sealant, the size of the area to be filled (the area to be sealed), etc. The sealant may be filled (injected) at high pressure or low pressure. When filling at high pressure, the pressure is preferably 0.5 MPa or more and 24 MPa or less. When filling at low pressure, the pressure is preferably 0.01 MPa or more and 0.5 MPa or less. From the viewpoint of improving the injectability of the sealant into the fine details of the area to be sealed, the pressure when injecting the sealant is preferably 0.1 MPa or more and 4 MPa or less.

[0116] FIG. 1 is a schematic diagram for explaining an example of a method for manufacturing a structure using a sealing material according to one embodiment of the present invention.

[0117] The structure 100 is a concrete structure. A sealing target (gap) 103 is formed between the structure 100 and the ground 102.

[0118] The sealant supply device 5 includes an injection gun 51 and a tank 52. The tank 52 is filled with the sealant.

[0119] First, a hole is drilled at a predetermined angle from the front to the back of the structure 100 to form the injection port 101. Next, the injection plug 1 is connected to the injection gun 51. After that, a compressor is used to fill (inject) the sealant into the part to be sealed 103 through the injection port 101 (placement process). Prior to the placement process, an injection plate may be installed on the front side of the structure so as to cover the periphery of the injection plug in order to prevent the sealant from leaking out of the front of the structure.

[0120] Next, if the resin in the sealant contains a curable resin, the curable resin in the sealant is cured (curing step). In this way, a structure can be obtained. The structure includes a cured product of the sealant as a filler filled in the part to be sealed. The cured product of the sealant is formed in the structure.

[0121] The cured product of the sealant preferably contains a cured product of the resin (curable resin) and the ion-releasing compound. The ion-releasing compound in the cured product of the sealant is a compound capable of releasing cations or anions. The ion-releasing compound in the cured product of the sealant is capable of generating a poorly water-soluble salt inside or on the surface of the cured product of the sealant. The ion-releasing compound in the cured product of the sealant is preferably dispersed in the cured product of the resin (curable resin).

[0122] In the above structure, the sealed area and its surroundings can be densified, and can be maintained in a stable state for a long period of time.

[0123] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to the following examples.

[0124] The following materials were prepared:

[0125] (resin) Curable resin A (moisture-curing modified silicone resin, "Infraguard 430S" manufactured by Sekisui Chemical Co., Ltd.) Curable resin B (two-component curing modified silicone resin, "Wacker Silicone" manufactured by Asahi Kasei Corporation, base resin (M4470) 96% by weight: curing agent (CATALYST T40) 4% by weight) Thermoplastic resin C (ethylene-vinyl acetate copolymer, Tosoh Corporation's "EVA Ultrathene #636")

[0126] (ion-releasing compounds) Compounds capable of releasing cations: Calcium lactate (Nacalai Tesque, average particle size 50 μm) Barium lactate (Fujifilm Wako Pure Chemical Industries, powder) Compounds capable of releasing anions: Sodium bicarbonate (Fujifilm Wako Pure Chemical Industries, Ltd., average particle size 107 μm) Sodium carbonate (Fujifilm Wako Pure Chemical Industries, Ltd., average particle size 100 μm) Sodium hydrogen phosphate (Fujifilm Wako Pure Chemical Industries, Ltd., powder) Sodium silicate (Nacalai Task "Sodium orthosilicate (Na4SiO4)")

[0127] Example 1 Sealant preparation: A sealant was obtained by mixing 100 parts by weight of curable resin A, 25 parts by weight of calcium lactate, and 25 parts by weight of sodium bicarbonate.

[0128] Preparation of specimen: Two concrete plates (150mm wide x 300mm deep x 40mm thick) were prepared, and a crack was created on the side of each plate (the 300mm deep x 40mm thick face) using a grinder, and the plates were arranged so that the cracked faces were in contact with each other. The boundary between the two concrete plates was designated as the sealing target, and the resulting sealant was applied to a width of 40mm and a thickness of 2mm to obtain a test specimen with the sealant placed on the concrete plate.

[0129] Example 2 A sealant was obtained by mixing 100 parts by weight of curable resin A and 30 parts by weight of sodium bicarbonate. A test specimen was obtained in the same manner as in Example 1, except that the obtained sealant was used.

[0130] Example 3 Sealant preparation: After mixing 96 parts by weight of the main component of curable resin B, 35 parts by weight of calcium lactate, and 35 parts by weight of sodium bicarbonate, 4 parts by weight of the curing agent of curable resin B was further mixed to obtain a sealant.

[0131] Preparation of specimen: A pipe (PVC, 50 mm diameter x 200 mm length) with one opening was prepared, and a release agent was applied to the inner surface of the pipe. The resulting sealant was injected into the pipe, and after 24 hours, it was removed from the pipe to obtain a cured sealant (sealed product) measuring 50 mm diameter x 200 mm length. Next, a concrete block (200 mm width x 200 mm depth x 150 mm height) was prepared, and a 50 mm diameter through-hole was drilled from the center of the top surface of the concrete block to the center of the bottom surface. Next, the cured sealant obtained was inserted into the through-hole of the concrete block, and a test specimen was obtained in which both ends of the cured sealant protruded from the top and bottom surfaces of the concrete block.

[0132] Example 4 A sealant was obtained by mixing 96 parts by weight of the main agent of curable resin B, 25 parts by weight of barium lactate, and 25 parts by weight of sodium carbonate, followed by further mixing with 4 parts by weight of the curing agent of curable resin B. A test specimen was obtained in the same manner as in Example 3, except that the obtained sealant was used.

[0133] Example 5 A sealant was obtained by mixing 96 parts by weight of the main agent of curable resin B, 25 parts by weight of calcium lactate, and 25 parts by weight of sodium hydrogen phosphate, followed by further mixing with 4 parts by weight of the curing agent of curable resin B. Test specimens were obtained in the same manner as in Example 3, except that the obtained sealant was used.

[0134] Example 6 Sealant preparation: 100 parts by weight of thermoplastic resin C, 25 parts by weight of calcium lactate, and 25 parts by weight of sodium hydrogen carbonate were melt-mixed in a twin-screw kneading extruder to obtain a sealing material (pellets).

[0135] Preparation of specimen: The resulting sealant (pellets) was extruded through a T-die using a twin-screw kneading extruder at 195°C to obtain a waterproof sheet (sealant, 400 mm wide x 1 mm thick). A sandstone block (400 mm wide x 400 mm deep x 150 mm thick) was placed inside a concrete formwork (400 mm wide x 400 mm deep x 400 mm thick), and the resulting waterproof sheet was placed on top of the sandstone block. Concrete was then poured onto the surface of the waterproof sheet opposite the sandstone block, cured for two months, and removed from the concrete formwork to obtain a test specimen consisting of a sandstone block layer, waterproof sheet, and concrete layer.

[0136] (Comparative Example 1) A sealing material and a test specimen were obtained in the same manner as in Example 1, except that no ion-releasing compound was used.

[0137] (Comparative Example 2) A sealing material and a test specimen were obtained in the same manner as in Example 3, except that no ion-releasing compound was used.

[0138] (Comparative Example 3) A sealant was obtained by mixing 96 parts by weight of the main agent of curable resin B, 35 parts by weight of calcium lactate, and 35 parts by weight of sodium silicate, followed by further mixing with 4 parts by weight of the curing agent of curable resin B. Test specimens were obtained in the same manner as in Example 3, except that the obtained sealant was used.

[0139] Comparative Example 4 A sealing material (pellets) and a test specimen were obtained in the same manner as in Example 6, except that no ion-releasing compound was used.

[0140] (evaluation) (1) Waterproof and durable The test specimens obtained in Examples 1, 2, and Comparative Example 1 were immersed in a water tank filled to a height of 30 mm for two months with the sealed area facing up, allowing the curable resin A to harden. The cured sealant was then peeled off from each test specimen, and the presence of particle deposition at the boundary between the two concrete plates was closely observed visually. The test specimens obtained in Examples 3 to 5 and Comparative Examples 2 and 3 were also immersed in a water tank filled to a height of 50 mm for two months with the through-holes parallel to the water surface. The cured sealant was removed from the concrete block, and the presence of particle deposition at the boundary between the concrete block and the cured sealant (the surface of the through-holes) and at both ends of the cured sealant was closely observed visually. Furthermore, the test specimens obtained in Example 6 and Comparative Example 4 were immersed in a water tank filled to a height of 100 mm for two months with the concrete layer facing up, and the presence of particle deposition in the voids within the sandstone block layer and on the surface of the concrete layer was closely observed visually. The voids inside the sandstone block layer were examined by cutting the specimen parallel to the depth direction and observing the cross section under a microscope.

[0141] For test specimens on which particles had precipitated, the specific gravity of the particles and their solubility in water at 20°C were measured using the methods described above. Waterproofing and durability were evaluated for specimens with a specific gravity of 2.0 or more and a solubility in water at 20°C of 1.0 x 10 -3 The determination was made based on the presence or absence of a poorly water-soluble salt (poorly water-soluble salt X) with a water content of less than 100 mol / L.

[0142] [Waterproof and durability criteria] ○: Poorly water-soluble salt X is generated ×: Poorly water-soluble salt X is not produced

[0143] In Examples 1 to 3 and 6, calcium carbonate (specific gravity: 2.71, solubility in water at 20°C: 1.5 × 10) was used as the poorly water-soluble salt X. -4 In Example 4, barium carbonate (specific gravity: 4.29, solubility in water at 20°C: 1.25 × 10 mol / L) was produced as the poorly water-soluble salt X. -4In Example 5, calcium phosphate (specific gravity: 3.14, solubility in water at 20°C: 6.5 × 10 mol / L) was produced as the poorly water-soluble salt X. -5 mol / L) was produced.

[0144] In Comparative Example 3, calcium silicate (specific gravity: 0.29, solubility in water at 20°C: 5.8 × 10 -4 mol / L), but because calcium silicate has a brittle crystal structure, it was not possible to densify the area around the through-hole and the area around the cured sealant, resulting in cracks. As a result, in Comparative Example 3, it was not possible to sufficiently improve the waterproofness and durability of the sealed area and its surroundings.

[0145] The composition of the sealing material and the results are shown in Tables 1 and 2 below.

[0146] [Table 1]

[0147] [Table 2] [Explanation of symbols]

[0148] 1...Injection plug 5...Feeding device 51...Injection gun 52...Tank 100...Structure 101…Inlet 102...ground 103...Sealing target part (gap)

Claims

1. The composition includes a resin and an ion-releasing compound capable of releasing cations or anions, The ion-releasing compound is capable of forming a poorly water-soluble salt, The specific gravity of the poorly water-soluble salt is 2.0 or more, The solubility of the poorly water-soluble salt in water at 20° C. is 1.0×10 -3 mol / L or less.

2. The sealant according to claim 1 , wherein the poorly water-soluble salt is calcium carbonate, barium carbonate, calcium phosphate, or iron hydroxide.

3. the ion-releasing compound comprises a compound capable of releasing a cation, 3. The sealant according to claim 1 or 2, wherein the compound capable of releasing cations is calcium silicate, tricalcium silicate, dicalcium silicate, calcium aluminate, calcium aluminoferrite, calcium hydroxide, calcium oxide, calcium acetate, calcium lactate, barium lactate, calcium sulfate, calcium chloride, calcium nitrate, or calcium bicarbonate.

4. the ion-releasing compound comprises a compound capable of releasing anions, 3. The sealant according to claim 1, wherein the compound capable of releasing anions is sodium hydrogen phosphate, potassium carbonate, potassium hydrogen carbonate, ammonium carbonate, ammonium hydrogen carbonate, sodium carbonate, sodium hydrogen carbonate, or calcium hydrogen carbonate.

5. The sealant according to claim 1 or 2, wherein the resin comprises a thermoplastic resin.

6. The sealant according to claim 1 or 2, wherein the resin comprises a curable resin.

7. an object to be sealed having a portion to be sealed; A sealing object disposed on the sealing target portion, A structure, wherein the sealing object is formed from the sealant according to claim 1 or 2.